2008
DOI: 10.1089/acm.2007.0765
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acid: A Role in the Management of Cardiac Arrhythmias?

Abstract: Additional studies are needed to evaluate the effect of omega-3 fatty acid before it can be routinely recommended for the management of arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
(41 reference statements)
0
5
0
1
Order By: Relevance
“…1.5 grams daily) are usually well tolerated with minimal adverse effects and interactions with other cardiovascular medications [20]. There may be a dose dependant effect of OM3FA in order to reach serum concentrations high enough to contribute to cardiac myocyte membrane stabilization and subsequently lower incidence of arrhythmias Overall it appears that the potential benefits of consumption of fish oils from fatty fish outweigh risks and that there are many potential roles in the symptomatic, physiologic, and pathologic reduction of cardiovascular disease [21].…”
Section: Discussionmentioning
confidence: 99%
“…1.5 grams daily) are usually well tolerated with minimal adverse effects and interactions with other cardiovascular medications [20]. There may be a dose dependant effect of OM3FA in order to reach serum concentrations high enough to contribute to cardiac myocyte membrane stabilization and subsequently lower incidence of arrhythmias Overall it appears that the potential benefits of consumption of fish oils from fatty fish outweigh risks and that there are many potential roles in the symptomatic, physiologic, and pathologic reduction of cardiovascular disease [21].…”
Section: Discussionmentioning
confidence: 99%
“…shifting the myocardium from a proarrhythmic state to an antiarrhythmic state. 28 However, the exact mechanisms of antiarrhythmic effects of omega-3 PUFA have yet to be clearly established.…”
Section: Eicosanoid Synthesismentioning
confidence: 99%
“…While some interventional studies reported either no effect or even promotion of arrhythmias in some subgroups of patients with heart disease (Raitt et al, 2005; Coronel et al, 2007; Den Ruijter et al, 2007; Cheng and Santoni, 2008), other studies have reported beneficial effects of ω-3-PUFAs on cardiac rhythm resulting in a reduction in the incidence of sudden cardiac death or mortality (London et al, 2007; Cheng and Santoni, 2008; Nodari et al, 2009). It seems that fish oil fatty acids may exert either pro- or anti-arrhythmic effects, probably depending on different underlying mechanisms for the arrhythmias.…”
Section: Introductionmentioning
confidence: 99%